MAIN CONCEPTS ABOUT DATA MINING AND ITS TENDENCIES FOR THE FUTURE - Almeida, Danilo Lima; Pinto, Giuliano Scombatti (Revista Interface Tecnológica, 2025)
Data mining is a crucial process for extracting useful knowledge from large amounts of data. By using statistical techniques, machine learning, and artificial intelligence, data mining allows the identification of patterns, trends, and relationships hidden in data. The objective of this article is to examine the main ideas of data mining, covering its phases, functions, and trends. A methodology was used for the literature review. The results demonstrated that the use of data mining is a fundamental part of the company, mainly in helping to attract customers and also in fraud prevention and cybersecurity. It is concluded that without its use, companies would not be able to act quickly to meet customer needs and improve how people interact with information, with innovation and strategic decision-making.